Analysis of Students' Mathematical Literacy Ability on Sequences and Series Material Through The Application of Problem Based Learning - Amalia, Kiki; Nuriadin, Ishaq (Universitas Wiralodra, 2023)
Mathematical literacy ability is the ability to understand and to use mathematics in various contexts to solve problems and explain how mathematics can be applied in everyday life. The aim of this study was to analyze students' mathematical literacy abilities in the material for sequences and series using problem based learning (PBL). The sample of this research was class XI SMA as many as 36 students and the subject was determined using purposive sampling. Tests, interviews, and documentation were used as data collection techniques. The research instrument was in the form of a mathematical literacy ability test on sequences and series material as well as interview guidelines that had been validated thereforehe instrument being suitable for use. The results of the study showed that the application of PBL to the matter of sequences and series was able to achieve students' mathematical literacy skills. Students can solve problems systematically and correctly even though there are operations such as multiplication or addition of numbers or variables an error occurs and students from both high and low categories do not write conclusions at the end of the problem. From the ability to choose a strategy students are able to identify the information contained in the question, but not yet fully students can decide on a strategy and apply facts, operations and structures in finding solutions related to story problems on sequences and series material.